Pitcher pot neourethral modification of ileal orthotopic neobladder achieves satisfactory long‐term functional and quality of life outcomes with low clean intermittent self‐catheterization rate. Issue 4 (4th June 2021) - Jaipuria, Jiten; Karimi, Ahmad Mamoon; Singh, Amitabh; Thapa, Bikash Bikram; Gupta, Shashikant; Sadasukhi, Nripesh; Venkatasubramaniyan, Manikandan; Pathak, Preeti; Kasaraneni, Priyatham; Khanna, Ashish; Narayan, Tushar Aditya; Sharma, Girish; et al.
Abstract: Objective: To describe a decade of our experience with a neo‐urethral modification of ileal orthotopic neobladder (pitcher pot ONB). Multiple investigators have reported similar modifications. However, long‐term longitudinal functional and quality of life (QOL) outcomes are lacking. Methods: Prospectively maintained hospital registry for 238 ONB patients comprising a mix of open and robotic surgery cohorts from 2007 to 2017, and minimum of 2 years of follow‐up was retrospectively queried. QOL was evaluated using Bladder Cancer Index (BCI). Longitudinal trends of QOL domain parameters were analysed. List of perioperative variables that have a biologically plausible association with continence, potency, and post‐operative BCI QOL sexual, urinary, and bowel domain scores was drawn. Variables included surgery type, Body Mass Index (BMI), T and N stage, neurovascular bundle (NVB) sparing, age, and related pre‐operative BCI QOL domain score. Prognostic associations were analysed using multivariable Cox proportional hazard models and multilevel mixed‐effects modeling. Results: The study comprised 80 and 158 patients who underwent open and robotic sandwich technique cohorts, respectively. Open surgery was associated with significantly higher "any" complication (40% vs 27%, P ‐value .050) and "major" complication rate (15% vs 11%, P ‐value .048). All patients developed a bladder capacity >400 cc with negligible post‐void residual urine, and all but one patient achieved spontaneous voiding by the end of study period (<1% clean intermittent self‐catheterization [CISC] rate). By 15 months, QOL for all three domains had recovered to reach a plateau. About 45% of patients achieved potency, and the median time to achieve day and night time continence was 9 and 12 months respectively. Lower age and NVBs spared during surgery were found to be significantly associated with the earlier achievement of potency, day and night time continence, as well as better urinary and sexual summary QOL scores. Conclusions: Pitcher pot neobladder achieves satisfactory long‐term functional and QOL outcomes with negligible CISC rate. Results were superior with incremental nerves spared during surgery.